Optimalisasi Fungsi Manajemen Kepala Ruangan Melalui Manajemen Burnout Staf Keperawatan di Masa Pandemi - Lia Dwi Jayanti; Hanny Handiyani; Krisna Yetti; La Ode A. Rahman; Nurdiana Nurdiana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to identify the management function of the head of the room, the level of staff burnout and develop problem solving solutions by preparing burnout management guidelines for nursing staff. The method used is a case study and analysis of results and implementation gaps with a discussion based on a literature review. The results showed that the perception of the head of the room related to the planning function was 53.7%, the organizing function was 59.3%, the manpower function was 53.7%, the directive function was 55.6% and the control function was 55.6%. The burnout level of nursing staff is in the medium category. The emotional exhaustion dimension scored 50.5%, the depersonalization dimension was 44.1% and the personal accomplishment dimension was 50.7%. In conclusion, the implementation of the draft guideline for burnout management can be carried out well. The involvement of the team, support from the Nursing Services Division and the Nursing Committee is needed in the preparation of the burnout management guide draft for nursing staff in hospitals. Keywords: Burnout, COVID-19, Function Management, Nurse Manager